Babaodan overcomes cisplatin resistance in cholangiocarcinoma via inhibiting YAP1 - Jiong Li; Xiangjun Ma; Faying Xu; Yuanliang Yan; Weiqing Chen (Taylor & Francis Group, 2024)
AbstractContext Cholangiocarcinoma with highly heterogeneous, aggressive, and multidrug resistance has a poor prognosis. Although babaodan (BBD) combined with cisplatin improved non-small cell lung cancer efficacy, its impact on overcoming resistance in cholangiocarcinoma remains unexplored.Objective This study explored the role and mechanism of BBD on cisplatin resistance in cholangiocarcinoma cells (CCAs).Materials and methods Cisplatin-resistant CCAs were exposed to varying concentrations of cisplatin (25-400 μg/mL) or BBD (0.25-1.00 mg/mL) for 48 h. IC50 values, inhibition ratios, apoptosis levels, DNA damage, glutathione (GSH) levels, oxidized forms of GSH, total GSH content, and glutaminase relative activity were evaluated using the cell counting kit 8, flow cytometry, comet assay, and relevant assay kits.Results BBD-reduced the cisplatin IC50 in CCAs from 118.8 to 61.83 μg/mL, leading to increased inhibition rate, apoptosis, and DNA damage, and decreased expression of B-cell lymphoma-2, p-Yes-associated protein 1/Yes-associated protein 1, solute carrier family 1 member 5, activating transcription factor 4, and ERCC excision repair 1 in a dose-dependent manner with maximum reductions of 78.97%, 51.98%, 54.03%, 56.59%, and 63.22%, respectively; bcl2-associated X and gamma histone levels were increased by 0.43-115.77% and 22.15-53.39%. The impact of YAP1 knockdown on cisplatin-resistant CCAs resembled BBD. GSH, oxidized GSH species, total GSH content, and glutaminase activity in cisplatin-resistant CCAs with BBD treatment also decreased, while YAP1 overexpression countered BBD's effects.Discussion and conclusion This study provides a scientific basis for BBD clinical application and provides a new direction for BBD biological mechanism research.